Time and material culture
1 online resource.
Keywords: "This edited volume offers a unique exploration into the ways in which Soviet culture and experience of time was unique, examining the temporalities expressed in the world of socialist things: from the objects of everyday life to urban architecture. Time and Material Culture will be useful to academics, upper-level undergraduates, and graduate students interested in twentieth century cultures of time"--